An analysis of a curriculum material in modern college algebra used by the University of the Philippines at Los Banos, and a proposed revision - Obungen, Silverio S.
The curriculum material "Modern College Algebra" which is used in the first year level of the University of the Philippines, Los Baños was analyzed in this study, in the light of the stated national goals of Education, the objectives of the University, and the latest developments in mathematics instruction. Furthermore, the study includes suggestions or revisions for the material